2015
DOI: 10.1007/s11517-015-1359-7
|View full text |Cite
|
Sign up to set email alerts
|

Toward the improvement in fetal monitoring during labor with the inclusion of maternal heart rate analysis

Abstract: Fetal heart rate (FHR) monitoring is used routinely in labor, but conventional methods have a limited capacity to detect fetal hypoxia/acidosis. An exploratory study was performed on the simultaneous assessment of maternal heart rate (MHR) and FHR variability, to evaluate their evolution during labor and their capacity to detect newborn acidemia. MHR and FHR were simultaneously recorded in 51 singleton term pregnancies during the last two hours of labor and compared with newborn umbilical artery blood (UAB) pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…We have previously found that the analysis of MHR and FHR interactions during labor may improve our clinical decisions (Gonçalves, Pinto, Silva, Ayres‐de‐Campos, & Bernardes, ; Pinto et al, ). More extensive studies are warranted to assess if the new findings obtained in the present study, on the influence of fetal gender on MHR and FHR interactions, may further improve our clinical decisions, as observed in other gender‐specific approaches to fetal assessment (Gonçalves, Bernardes, & Ayres‐de‐Campos, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously found that the analysis of MHR and FHR interactions during labor may improve our clinical decisions (Gonçalves, Pinto, Silva, Ayres‐de‐Campos, & Bernardes, ; Pinto et al, ). More extensive studies are warranted to assess if the new findings obtained in the present study, on the influence of fetal gender on MHR and FHR interactions, may further improve our clinical decisions, as observed in other gender‐specific approaches to fetal assessment (Gonçalves, Bernardes, & Ayres‐de‐Campos, ).…”
Section: Discussionmentioning
confidence: 99%
“…Gonçalves, Pinto, Silva, Ayres-de-Campos, and Bernardes (2016) assessed MHR in addition to conventional FHR monitoring, reporting a significant increase in both FHR and MHR linear indices during labor, while the opposite occurred with entropy indices. Additionally, a sensitivity value of nearly 100% and specificity of 89.1% were achieved with the inclusion of MHR on bivariate analysis, suggesting that simultaneous monitoring of maternal and fetal heart rates may improve the identification of fetal acidemia in comparison with exclusive FHR monitoring (Gonçalves, Pinto, Silva, Ayres-de-Campos, & Bernardes, 2016). Despite the increasing focus in MHR monitoring during labor, less is known about the effect of fetal gender on MHR tracings.…”
mentioning
confidence: 99%
“…The highest observed value of 0.70 using SampEn(2,0.1) in H 2 regarding fetal acidemia, and of 0.74 using mHR in H 2 in the detection of operative vaginal delivery, opens the possibility of single or combined use of MHR and FHR indices, in the identification of these situations. The discriminatory capacity of these indices may be higher for detection of fetal acidemia when considering a multivariate approach (Gonçalves et al 2016 ). However, the objective of maximizing discriminatory performance was not under the scope of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Entre los estudios clínicos hechos a partir de la VFC se encuentra la detección de infarto agudo de miocardio (IAM) 30 falla cardíaca 31 , trasplante cardíaco, disfunción miocárdica 28 , insuficiencia cardíaca crónica 32 e infecciones [33][34][35][36][37] . El estudio de las características de la variabilidad cardíaca no sólo se ha utilizado en adultos sino también en la etapa fetal 38 , y neonatal 3,4 . Estudios han señalado asociaciones entre cambios de la VFC y algunos estados indeseados que implican riesgo de mortalidad para los neonatos como la sepsis 2,5 .…”
Section: Discussionunclassified